Citrandarins initial growth for production of citrus seedlings : Citrandarins initial growth for production of citrus seedlings - Barbosa, Vitor Ribeiro (2023)
In the Brazilian orchards there is few genetic diversity of rootstocks, leaving the citrus fruit sector more susceptible to adverse biotic and abiotic factors, such as pests and diseases and sensitivity to water deficit, which cause decrease of productivity and fruit quality. The present study aimed to evaluate the initial growth of 24 Citrandarin hybrids rootstock (Tangerina sunki vs. Poncirus trifoliata), in a greenhouse at the “Sylvio Moreira” APTA Citrus Center by periodic measurements of plant height and stem diameter. The Citrandarins evaluated showed the same growth behavior in relation to plant height. There was increase in the average height of plants over time, making them suitable for the grifting process. The Citrandarins named 47, 152, 158, 232 and 304 did not show stem growth in the evaluated period. New studies are needed after the grifting in the main scion varieties in these citrandarins to verify the transmission of vigor, precocity, compatibility and others characteristic of economic interest for citriculture.